2022
DOI: 10.3390/ani12192616
|View full text |Cite
|
Sign up to set email alerts
|

Acetate-Induced Milk Fat Synthesis Is Associated with Activation of the mTOR Signaling Pathway in Bovine Mammary Epithelial Cells

Abstract: Acetate is a precursor substance for fatty acid synthesis in bovine mammary epithelial cells (BMECs), and the mTOR signaling pathway plays an important role in milk fat synthesis. However, the mechanism of the regulatory effects of acetate on lipogenic genes via the mTOR signaling pathway in BMEC remains unknown. We hypothesized that acetate can enhance the expression of lipogenic genes and triglyceride (TG) production by activating the mTOR signaling pathway in BMECs. Therefore, the aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…According to the evidence that PI3K/mTOR signaling pathway plays an important role in milk fat synthesis, we speculated that AG may promote TAG synthesis in BMECs via this signaling pathway. We treated BMECs with varying concentrations of AG for 24 h to detect the activation of the PI3K/mTOR signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…According to the evidence that PI3K/mTOR signaling pathway plays an important role in milk fat synthesis, we speculated that AG may promote TAG synthesis in BMECs via this signaling pathway. We treated BMECs with varying concentrations of AG for 24 h to detect the activation of the PI3K/mTOR signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies have suggested that acetate esters promote milk fat biosynthesis by enhancing fatty acid biosynthesis in a dose-dependent manner [167]. Recently, studies have demonstrated that acetate esters promote the expression of ACCA and FAS proteins via the mTOR-S6K1 signaling pathway to increase milk fat biosynthesis [168].…”
Section: Modulation Of Milk Fat Synthesis Via Functional Supplementsmentioning
confidence: 99%